(untitled) (Research, Society and Development, 2022)
The monitoring of the child’s growth is carried out by nursing professionals in Primary Health Care (PHC), where data on: weight, height and body mass index (BMI) are evaluated. It also assesses development, understood as a hereditary set with interactions in a child’s daily life, influencing the neurological system such as: speaking, motor, cognitive and psychosocial growth. This study aims to analyze the Child Growth and Development Program in Basic Units of Health through the perception of caregivers and nursing professionals. This is a descriptive and explanatory research, having as a procedure the field survey and of a qualitative nature, which was carried out with 6 professionals and 11 guardians, through a semi-structured interview carried out from August to September 2022 in four PHC units in a municipality in the interior of Bahia. Information was obtained through semi-structured interviews, and the data collected were organized according to Bardin’s thematic analysis. The results were separated into study categories divided into two groups, guardians and professionals. Accompaniment in the childcare consultation becomes essential in the lives of children, so that they have a healthy development. Since nursing professionals have a fundamental role in promoting the monitoring of the child’s health. There are gaps in communication between nursing professionals and guardians, since they themselves do not understand the importance of carrying out the childcare consultation, even adhering to the consultation.